2013
DOI: 10.4237/transportes.v21i1.566
|View full text |Cite
|
Sign up to set email alerts
|

Utilização dos testes estatísticos de Kolmogorov-Smirnov e Shapiro-Wilk para verificação da normalidade para materiais de pavimentação

Abstract: Resumo: Na pavimentação, é comum tratar os dados obtidos em ensaios à luz de conceitos da estatística clássica, que consideram que um conjunto de dados possui distribuição Normal e utilizam os parâmetros média e desvio padrão na análise dos dados. O presente trabalho se propõe a verificar a aderência à distribuição Normal de dados oriundos de alguns ensaios de materiais para pavimentação: densidades aparente e real e absorção do agregado graúdo, densidade aparente e volume de vazios de corpos de prova de mistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 3 publications
0
8
0
11
Order By: Relevance
“…According to Table 4, only the residues of the neural network 3 (MLP 12: 12-21-1: 1) showed normality. Taking as reference the studies of TORMAN et al (2012) and LOPES et al (2013), the non-significance in normality tests gives it greater reliability to this network. However, the t-test indicated that there are no differences between the measured fuel consumption values and the estimated by the four networks (Table 5).These results allow to affirm that the four networks are appropriate, although the third formed by a single hidden layer with twenty-one neuron is presented as the most suitable for predicting this consumption, depending on the variables that characterize the soil, the implement type in combination with the tillage system and operating conditions for mechanized set.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 4, only the residues of the neural network 3 (MLP 12: 12-21-1: 1) showed normality. Taking as reference the studies of TORMAN et al (2012) and LOPES et al (2013), the non-significance in normality tests gives it greater reliability to this network. However, the t-test indicated that there are no differences between the measured fuel consumption values and the estimated by the four networks (Table 5).These results allow to affirm that the four networks are appropriate, although the third formed by a single hidden layer with twenty-one neuron is presented as the most suitable for predicting this consumption, depending on the variables that characterize the soil, the implement type in combination with the tillage system and operating conditions for mechanized set.…”
Section: Resultsmentioning
confidence: 99%
“…The exponential smoothing method of HoltWinters was used to smooth and eliminate any noise of the time series 13 . After the Kolmogorov-Smirnov test indicated normal distribution of data, the variables PM 10 , relative humidity, air temperature, and hospital admissions due to MS were correlated using Pearson's model 14,15 . Although many studies that correlate air pollution and meteorological variables with diseases use the Poisson family of generalized linear models (MLG), in this study we used multiple linear regression 3,16,17 .…”
Section: Materials and Methods O Meteorological Datamentioning
confidence: 99%
“…Afterwards, the statistical assumptions of Independence, Normality and Homoscedasticity were checked [37]. In order to assess if the data were normally distributed, the test of Shapiro-Wilk (1965) [39] was used. The theory of Shapiro-Wilk (1965) is based on two hypotheses: Ho the variable's data follow normal distribution and H1 the variable's data do not follow normal distribution.…”
Section: Multivariate Analysis Of Variance (Manova)mentioning
confidence: 99%